Implementing case-based reasoning technique to software requirements specifications quality analysis - Jani H.M.; Mostafa S.A. (Advanced Institute of Convergence Information Technology, 2023)
Software Requirements Specifications (SRS) or software requirements are basically an organization's interpretation of a customer's system requirements and dependencies at a given point in time. Basically, good quality SRS will lead to good quality software product. It is widely known that companies pay much less to fix problems or defects that are found very early in any software development life cycle (SDLC). In this study, the Software Quality Assurance (SQA) audit technique is applied to determine whether or not the required standards and procedures within the requirements specifications phase are being followed closely. The proposed online SRS quality analysis system ensures that software requirements among others are complete, consistent, correct, modifiable, ranked, traceable, unambiguous, and understandable. The system interacts with the developer through a series of questions and answers session, and requests the developer to go through a checklist that corresponds to the list of desirable characteristics for SRS. The Case-Based Reasoning (CBR) technique is used to evaluate the requirements quality by referring to previously stored software requirements quality analysis cases (past experiences). CBR is an AI technique that reasons by remembering previously experienced cases. It assists in making the SRS quality analysis process more efficient. An executable prototype is developed to demonstrate several selected features and results of the proposed SRS quality analysis system.